2021
DOI: 10.1097/olq.0000000000001499
|View full text |Cite
|
Sign up to set email alerts
|

High Number of Positive Rapid Plasma Reagin With Low Titers Using the Automated AIX 1000 RPR System

Abstract: This study evaluated the performance of manual rapid plasma reagin (RPR) and automated AIX1000 RPR tests for the diagnosis of syphilis. Manual RPR showed a 3% reactive result compared with 5.8% for the automated test mainly because of RPR reactive results with low titers not confirmed by Treponema pallidum particle agglutination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Sanfilippo et al 10 showed a false-positive rate of 43.6% for the RPR-A at an initial screening, which was solved by including a second screen at the time of titer determination. Also, Palavecino et al 13 registered an increase in positive samples with a low RPR-A titer (5.8%) compared with manual RPR (3%), of which 57% were false positive. The high number of false-positive results is likely related to the low prevalence in these studies and is likely lower when using the reverse algorithm.…”
Section: Discussionmentioning
confidence: 98%
“…Sanfilippo et al 10 showed a false-positive rate of 43.6% for the RPR-A at an initial screening, which was solved by including a second screen at the time of titer determination. Also, Palavecino et al 13 registered an increase in positive samples with a low RPR-A titer (5.8%) compared with manual RPR (3%), of which 57% were false positive. The high number of false-positive results is likely related to the low prevalence in these studies and is likely lower when using the reverse algorithm.…”
Section: Discussionmentioning
confidence: 98%